Polemik Kebebasan Berpendapat dalam Perspektif Undang-Undang ITE - Musfala Yudha (Jurnal Litigasi Amsir, 2022)
Violations in the use of social media are troubling to the community, especially teenagers, and the government expects individual activity when criticizing the government. However, this statement caused controversy among all circles. This paper aims to find out the public's response to the government, which demands to be criticized but is threatened by the ITE Law. And discuss the form of legal guarantees so that the public, in criticizing the government, can be protected from criminal sanctions and efforts to prevent the misuse of social media as a means of committing crimes. The research was conducted using a descriptive method. The existence of the ITE Law makes individuals worry when criticizing or making suggestions to the government due to the reduced guarantee of freedom of expression when criticizing the government with social media and explaining Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, as well as efforts to prevent the occurrence of information technology crimes through social media.